QUALITY OF LIFE IN CHILDREN AND ADOLESCENTS WITH CONGENITAL ADRENAL HYPERPLASIA - Suleman, Fawad; Noor, Noshaba; Iqbal, Samiya; Sher, Zainab; Noor, Mohsina (Journal of Pakistan Psychiatric Society, 2024)
BACKGROUND: Congenital Adrenal Hyperplasia (CAH) is a hereditary endocrine condition, defined by insufficiency of enzymes that cause abnormalities in adrenal steroidogenesis, resulting in adrenal insufficiency and hyperandrogenism. In adults, Congenital Adrenal Hyperplasia has been linked to a lower quality of life (QoL). However, research in children has yielded inconsistent results. Therefore, this study was conducted to investigate the impact of CAH on the quality of life of children and adolescents.OBJECTIVE: To assess the Quality of Life of children and adolescents with Congenital Adrenal Hyperplasia (CAH).METHODS: It was a descriptive cross-sectional study with six months duration. We enrolled all children and adolescents in the range of 8 to 18 years of age who have been diagnosed with CAH. The World Health Organization Quality of Life-BREF (QOL-BREF) instrument was used for data collection. Four health domains including physical, psychological, social, and environmental areas were assessed, with higher transformed scores indicating better QOL. Data was entered on SPSS Version 23.RESULTS: Our study population comprised of 30 children and adolescents with a mean age of 12.75 ±3.23 years. Mean transformed scores of physical, psychological, social, and environmental health domains were 31.37±12.15, 45.13±12.50, 34.8±20.49 and 37.6± 12.06 respectively.CONCLUSION: The quality-of-life score in our population was relatively low in the physical and social domains of health as compared to psychological and environmental health domains. Larger community-based studies are required to further elaborate the causes and remedies of poor quality of life in children and adolescents.